2014
DOI: 10.1038/icb.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Jagged‐1 combined with blockade of CD40 pathway prolongs allograft survival

Abstract: Dendritic cells (DCs) have the tolerogenic potential to regulate adaptive immunity and induce allografts acceptance. Here we investigated whether blockade of the CD40 pathway could enhance the immune tolerance induced by DC2.4 cells modified to express Jagged-1 (JAG1-DC) in heart transplantation. Results showed that JAG1-DC treatment combined with anti-CD40L monoclonal antibody (mAb) administration significantly prolonged cardiac allograft survival in mice, with long-term survival (>110 days) of 50% of the all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Although Dll1‐overexpressing L cells delayed allograft rejection in a CD8 + T cell–dependent manner, it is unclear whether the effects were the result of direct engagement of Dll1 with Notch receptor in T cells. Similar observations were reported recently on in vivo transfer of a Jag1‐transduced DC line in combination with CD40 blockade . Altogether, these studies suggested that inducing artificially high Notch signals in T cells could generate a state of antigen‐specific tolerance.…”
Section: Early Work On Notch Signaling In T Cell Alloreactivity and Tsupporting
confidence: 87%
“…Although Dll1‐overexpressing L cells delayed allograft rejection in a CD8 + T cell–dependent manner, it is unclear whether the effects were the result of direct engagement of Dll1 with Notch receptor in T cells. Similar observations were reported recently on in vivo transfer of a Jag1‐transduced DC line in combination with CD40 blockade . Altogether, these studies suggested that inducing artificially high Notch signals in T cells could generate a state of antigen‐specific tolerance.…”
Section: Early Work On Notch Signaling In T Cell Alloreactivity and Tsupporting
confidence: 87%
“…27 Other studies reported that transgenic expression of Jag1 by Epstein-Barr virus-positive lymphoblastoid cell lines induced antigen-specific Treg cells and thereby reduced the alloreactivity of T cells. 26,45 Moreover, Lin et al 46 transduced the Jag1 gene into the DC2.4 cell line by an adenovirus, and they demonstrated that blockade of the CD40 pathway enhanced the immune tolerance by Jag1-overexpressing DC2.4 cells during heart transplantation. Collectively, these results indicate that Jag1 signaling is critical for inducing the generation of Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between both studies may be explained by differences in the generation protocols as well as the detection techniques used. Dex also induced several molecules associated with regulation of immune responses involving Treg and effector T-cell functions (JAG1, TBXAS1, and MERTK) ( 49 , 50 ), DC differentiation and function (IRAK3, GILZ, C1Q, and STAB1) ( 28 , 51 , 52 ) and suppression of inflammatory signaling (MAP3K8/TPL-2, FCGR2B, and VDR). Functional enrichment analysis showed that Dex treatment of moDCs also induced the expression of genes related to the complement system pathway.…”
Section: Discussionmentioning
confidence: 99%